Cooking autonomy: a multilevel conceptual model on healthy home cooking - Mariana Fernandes Brito de Oliveira; Inês Rugani Ribeiro de Castro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
The empowerment of home cooking has been recently approached in the literature as pertaining to cooking skills and the capacity to overcome social, physical, and economic obstacles. However, thus far no studies have related the State's role in this important health-promoting home practice, namely healthy cooking. We aim to elaborate on the concept and develop a multilevel conceptual model of cooking autonomy (CMCA) in order to relate the State's role in healthy home cooking. This is a theoretical-conceptual study consisting of three phases: conceptual elaboration, expert panel consultation, and content validity of the CMCA developed in this study. A comprehensive literature review worked as the theoretical and conceptual basis, featuring Amartya Sen's human capability approach. A total of 28 experts issued their opinions in listening workshops and interviews. Cooking autonomy was defined as the capacity to think, to decide, and to act to prepare meals from scratch, influenced by interpersonal relations, environment, cultural values, access to opportunities, and guarantee of rights. The CMCA has six levels, differing according to the degree of participation of an individual. We also present two charts with examples of the agent's practices and actions that can be developed by the State in the public policy sphere. As a pioneering model in the international literature, the CMCA provides the conceptual basis for the development of studies and interventions on cooking autonomy, focusing not only on individual skills, but also on the role of public policies for healthy home cooking.